Caracterização da alteração hidrotermal no alvo Coelho Central, depósito aurífero Pedra Branca, sequência Serra das Pipocas, maciço de Troia, com base em estudos isotópicos (O, H, S e C) e inclusões fluidas. - LIMA, Rafael Guimarães Corrêa (Universidade Federal do Pará, 2019)
The gold mineralization of Pedra Branca deposit is associated with rhyacian metavolcanic rocks of Serra das Pipocas Greenstone Belt, at the Archean–Paleoproterozoic Troia Massif, in Borborema Province, NE of Brazil. The deposit comprises four mineralized targets, Mirador, Queimadas, Igrejinha and Coelho Central and has been classified as a hypozonal orogenic gold deposit based on the geological context, types of hydrothermal alterations and isotopic data obtained for Mirador and Queimadas targets. At Coelho Central target, the main gold host rocks are ilmenite- and garnet amphibolites (after mafic volcanic rocks). Some gold occurrences has been recognized in altered metadacites and metatonalites intrusive lenses. Hydrothermal and mineralized zones show mineral assemblages formed under amphibolite facies conditions. (i) calc-silicate veinlets (diopside, titanite, calcite, epidote and sulfides), (ii) hornblende, albite, biotite and garnet veinlets with pyrrhotite and gold, (iii) biotite-rich potassic alteration containing pyrrhotite, gold and tellurides and (iv) quartz veins are the main types of ore-related alterations. In addition, (v) epidote, titanite and calcite pockets, (vi) chloritization and (vii) pyrite-rich fissural carbonatization are the late and no ore-related alterations that marks a ductile-brittle deformation, probably under greenschist facies conditions. Gold occurs predominantly as inclusions in pyrrhotite, chalcopyrite, pentlandite and Co-pentlandite indicating their association with sulfur species and subordinately as free-milling microparticles in quartz veins. The metallic association of sulfidation zones also includes abundant Ag, Bi, Ni and Pb tellurides. Oxygen and hydrogen geothermometry for hydrothermal silicates yielded temperatures from 484 to 586 ºC for the gold-related alterations. The fluid isotopic composition in equilibrium with hydrothermal silicates (quartz, hornblende, biotite, tourmaline and titanite) shows values of δ18O (+6.8 to + 10.7 ‰) and δD (-58.4 to -35.5 ‰), as well as the values of δ34S in sulfides (-3.1 and +2.7 ‰) and δ13C for calcite (-11.1 to -5.8 ‰), indicative of deepseated magmatic-hydrothermal fluid, with possible interaction and mixing with fluids of the greenstone sequence. Fluid inclusions assemblages in quartz veins show the predominance of CO2 inclusions, with a density up to 1.15 g/cm3 and up to 15 mol% of CH4, coexisting with N2 inclusions, and also with low salinity (< 9.7 wt% NaCl equiv.) H2O-CO2-NaCl and H2O-NaCl-FeCl2±MgCl2 varieties. The petrographic and microthermometric criteria suggest the immiscibility of a CO2-H2O-NaCl-N2-CH4 fluid as responsible for the generation of the observed inclusions. Desestabilization of complexes such as Au(HS)-2 and precipitation of gold and associated metals occurred by immiscibility, fluid-rock interaction, and changes in redox conditions and fluid pH, between 2.2 and 5,5 kbar (6.3 to 16.0 km). A H2O-NaCl-CaCl2 latter fluid was the responsible for the calcite, with pyrite and sphalerite precipitation in fractures and faults. The characteristics presented above allow us to ratify the Coelho Central target and Pedra Branca deposit as a hypozonal gold mineralization formed under amphibolite facies conditions, from CO2-rich deep-seated magmatic fluids that interacted with the metamorphic sequence of Serra das Pipocas Greenstone Belt and precipitated gold and associated metals.